Achieving Acceptable Dredge Availability at Grey River Gold Mining Limited (The Australasian Institute of Mining and Metallurgy, 1989)
The achievement of high availability of the Grey River Gold Mining Limited's alluvial gold dredge is a tortuous task which will rely upon the dedication of all staff employed at Grey River Gold Mining Limited (GRGML). The persistent adoption of new technology and better operating procedures, combined with a strong commitment to preventative and predictive maintenance, is necessary. The Grey River Gold Mining Limited alluvial gold dredge is operating in a relatively low grade alluvial gold deposit and hence relies on a high throughput of ore to be profitable. To achieve the required high material throughput the dredge incorporates an overburden removal system which operates simultaneously with a conventional bucketline system.   The overburden system incorporates a cutter wheel and suction pump configuration which is dedicated to removing the low grade (5 mg gold/m3 gravel) overburden. The bucketline conveys the richer grade payzone gravels (up to 890 mg/m3 gravel) to the recovery plant mounted onboard the dredge. The horizon for the overburden system approximates 15 m and the payzone terminates at the interface of the old man rock and the alluvial gravels at a variable depth averaging 22 m.   From a mechanical engineering perspective the dredge is a machine comprised of two materials handling systems which are controlled by Operations Staff and electronic process control systems.   The availability of such a materials handling system is a function of four variables: 1. The environment that the machine operates in. 2. The ability of the people operating the machine. 3. The design of the mechanisms, the configuration that they are grouped in and the effectiveness of the process control systems which control the mechanisms. 4. The procedures utilised to predict the performance of the machines and the skill of staff to analyse that data and carry out effective maintenance.